Quercus suber cork extract displays a tensor and smoothing effect on human skin: an in vivo study. - Coquet, C.; Bauza, E.; Oberto, G.; Berghi, A.; Farnet, A. M.; Ferré, E.; Peyronel, D.; Dal Farra, C.; Domloge, N. (Drugs under experimental and clinical research, 2005)
Recently, it has become indispensable for anti-aging active ingredients to provide a visible and immediate smoothing antiwrinkle effect. In Quercus suber, suberin is the most important structural component of cork cell walls. Studies have shown that suberin is made up mostly of hydroxycarboxylic acids and that it is endowed with many special mechanical and chemical properties that evoke a possible smoothing effect on the surface of the skin. Therefore, we were interested in investigating the effect of this cork extract on the skin's surface in a double-blind clinical study. The study was conducted in 15 healthy volunteers, aged 22 to 52 years. The volunteers applied a gel formula with 3% of cork extract, or placebo gel, on each forearm. Skin surface roughness was evaluated visually by pictures and by silicone replicas 1 and 2 h after application, followed by statistical analysis using the matched-pairs McNemar statistical test. McNemar analysis of the pictures revealed that application of cork extract on the skin resulted in a highly significant reduction of roughness 1 h after application. This effect was observed in 73.3% of volunteers. Two hours after cork extract application, a highly significant improvement of skin roughness was found in 78.6% of volunteers. Moreover, silicone replica treatment confirmed significant improvement in average of roughness at 2 h. These results demonstrate that cork extract provides a remarkable and highly significant tensor and smoothing effect on the skin, which could be of great use in anti-aging skin care products.
Journal Article,Randomized Controlled Trial,Journal Article,Randomized Controlled Trial,The following values have no corresponding Zotero field: pub-location: Vincience Research Center, Sophia Antipolis, France.
Keywords: 2; 3-friedelanol; 6-heptanediol; Quercus suber L.; suberin; Terpens